In situ correction of various β-thalassemia mutations in human hematopoietic stem cells - Yang, Yinghong; He, Lina; Xie, Yingjun; Zhu, Lifen; Wu, Jianfeng; Fan, Yong; Yang, Yi; Sun, Xiaofang (Frontiers in Cell and Developmental Biology, 2024)
β-thalassemia (β-thal) is the most common monogenic disorder caused by various mutations in the human hemoglobin β (HBB) gene and affecting millions of people worldwide. Electroporation of Cas9 and single-guide RNA (sgRNA)–ribonucleoprotein (RNP) complex-mediated gene targeting in patient-derived hematopoietic stem cells (HSCs), followed by autologous transplantation, holds the promise to cure patients lacking a compatible bone marrow donor. In this study, a universal gene correction method was devised to achieve in situ correction of most types of HBB mutations by using validated CRISPR/sgRNA–RNP complexes and recombinant adeno-associated viral 6 (rAAV6) donor-mediated homology-directed repair (HDR) in HSCs. The gene-edited HSCs exhibited multi-lineage formation abilities, and the expression of β-globin transcripts was restored in differentiated erythroid cells. The method was applied to efficiently correct different mutations in β-thal patient-derived HSCs, and the edited HSCs retained the ability to engraft into the bone marrow of immunodeficient NOD-scid-IL2Rg−/− (NSI) mice. This study provides an efficient and safe approach for targeting HSCs by HDR at the HBB locus, which provides a potential therapeutic approach for treating other types of monogenic diseases in patient-specific HSCs.